Completion of phase 2b trial of etranacogene dezaparvovec gene therapy in patients with hemophilia B over 5 years - Annette von Drygalski; Esteban Gomez; Adam Giermasz; Giancarlo Castaman; Nigel S. Key; Susan U. Lattimore; Frank W. G. Leebeek; Wolfgang A. Miesbach; Michael Recht; Paul E. Monahan; Sandra Le Quellec; Steven W. Pipe (Blood Advances)
Abstract: Etranacogene dezaparvovec (CSL222, formerly AMT-061) is a recombinant adeno-associated virus serotype 5 (AAV5) vector containing the highly active factor IX (FIX) Padua variant controlled by a liver-specific promoter. This phase 2b, open-label, single-dose, single-arm, multicenter trial evaluated the efficacy and safety of etranacogene dezaparvovec. Three adult participants with severe or moderately severe hemophilia B (FIX ≤2%) and AAV5-neutralizing antibodies received a single IV dose (2 × 1013 genome copies per kg) of etranacogene dezaparvovec. The primary end point of FIX activity ≥5 IU/dL at 6 weeks was met (mean, 30.6 IU/dL). Secondary end points included bleed frequency, FIX concentrate use, and adverse events. Here, we report the end-of-study 5-year outcomes. After administration, mean (range) FIX activity increased to 40.8 IU/dL (31.3-50.2) at year 1 and was maintained at 45.7 IU/dL (39.0-51.2) at year 5. Mean annualized bleeding rate (all bleeds) was 0.14 for the cumulative follow-up period years 0 to 5. Two participants had 5 bleed-free years after treatment. Per protocol, 1 participant received episodic FIX replacement therapy after treatment for elective surgeries, 2 bleeding episodes, and 2 single self-administered infusions for unreported reasons. All participants discontinued and remained free of FIX prophylaxis. During the 5-year study period, there were no clinically significant elevations in liver enzymes, requirement for steroids, FIX inhibitor development, thrombotic complications, or late-emergent safety events in any participant. Five years after administration, etranacogene dezaparvovec was effective in adults with hemophilia B with a favorable safety profile. Participants are eligible to participate in an extension study (ClinicalTrials.gov identifier: NCT05962398) for 10-year additional follow-up. This trial was registered at www.clinicaltrials.gov as #NCT03489291.